2020
DOI: 10.1038/s41419-020-2355-x
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-educated B cells promote renal cancer metastasis via inducing the IL-1β/HIF-2α/Notch1 signals

Abstract: While B cells in the tumor microenvironment (TME) might play important roles in cancer progression, their impacts on the renal cell carcinoma (RCC) metastasis remained unclear, which drew our attention to further explore. We found that RCC tissues could recruit more B cells than the surrounding normal renal tissues from human clinical RCC samples. Wound healing assay, transwell assay and 3D invasion assays demonstrated that recruited B cells, also known as tumor-educated B cells (TEB), could significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…B-cells are more easily recruited in renal carcinoma tissues than in normal renal tissues. The interaction between B-cells and cancer cells allows IL-1β secretion, which is responsible for renal cancer cell migration, through HIF-2α and Notch1 pathways [ 216 ]. Production of IL-1β by cancer cells or neighboring cells can activate many molecular pathways that lead to cancer cell migration.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…B-cells are more easily recruited in renal carcinoma tissues than in normal renal tissues. The interaction between B-cells and cancer cells allows IL-1β secretion, which is responsible for renal cancer cell migration, through HIF-2α and Notch1 pathways [ 216 ]. Production of IL-1β by cancer cells or neighboring cells can activate many molecular pathways that lead to cancer cell migration.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…1 b) [ 19 , 69 ]. Recent studies have shown that up-regulated expression of interleukin-1β (IL-1β) secreted by B cells promotes the activation of HIF-2α, and HIF-2α activation further promotes the activation of delta like canonical Notch ligand 4 (DLL4) signaling, and finally interact with neurogenic locus notch homolog (Notch) to form the IL-1β/HIF-2α/Notch 1 axis [ 70 ]. Collectively, various mechanisms drive HIF signaling activation in low oxygen tensions to maintain the state of various cancer cell types, and TNF-α interacts with HIF signaling provides a preferable and typical example.…”
Section: Canonical and Non-canonical Regulation Of Hif Signalingmentioning
confidence: 99%
“…[ 4 , 5 ]. Tumor cells and the components of TME, including CD8 + T cells [ 6 , 7 ], CD4 + T cells [ 8 , 9 ], NK cells [ 10 ], dendritic cells [ 11 , 12 ], B cells [ 13 , 14 ], macrophages [ 15 ], FOXP3 [ 16 ], and Collagen I [ 17 ] have close correlations to tumor treatment and prognosis. In past decades, due to the limitations of tools and clinical methodologies, it was difficult to analyze multiple components and assess tumor heterogeneity of the TME.…”
Section: Introductionmentioning
confidence: 99%